History of the Second World War - Hart, B. H. Liddell (London Pan Books, 1970)
One-volume military history of World War II, written by a British historian.
Include Maps and Index
Keywords: Military Campaigns -- Guerre Mondiale, 1939-1945 -- World War (1939-1945)